DEVELOPMENT OF GENERAL ENDURANCE IN YOUNG CHILDREN THROUGH SPECIAL EXERCISES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
In the article, the results of positive effects of physical exercises, healing forces of nature, and hygienic factors on physical development and strengthening of their health, training tools aimed at educating children's general endurance during training sessions with children are justified. The changes that occur in the child through natural factors aimed at preventing physical stress and exhaustion are shown. A number of new cases have been included in the methodology of training endurance of young athletes.